Можливості та перспективи геотермальної енергетики в Україні - Однороб, В. О. (ХНУРЕ, 2025)
Geothermal energy is the internal heat energy of the Earth. It is a type of clean renewable energy. It emits very few greenhouse gases compared to traditional sources such as coal or oil. The theoretical potential of geothermal energy is estimated at around 100 GW, but the economically viable potential is lower and depends on technology and market conditions.
Keywords: геотермальна енергетика; перспективи енергетики